Prosthetic treatment with dental implants - Koszuta, Agnieszka; Szymańska, Jolanta; Szpak, Piotr (Polish Journal of Public Health, 2012)
Dental implant prosthetic therapy enables a fully functio-nal and aesthetic supplement of the missing teeth. In recent years, implant-supported prostheses have enjoyed a growing popularity in Poland; the treatment is provided as a full-price therapeutic procedure, mainly in private dental practices.On the basis of the scientific literature data, the paper presents, in outline, the history of implantology in Poland, as well as the essential information on dental implantation, describing in detail indications and contraindications for the use of implants. The current status of knowledge on the failure of this type of treatment is presented, taking into account the influence of patients’ age, general illnesses, including osteoporosis, diabetes, hypertension, as well as dental and medical factors. Special attention was paid to pain as an important symptom of complications in dental implant treatment. In addition, factors affecting decisions about the treatment of missing teeth with dental implants were discussed.